Advances in Cryptology EUROCRYPT 2010 29th Annual International Conference on the Theory and Applications of Cryptographic Techniques, French Riviera, May 30 June 3, 2010. Proceedings - Gilbert, Henri. (Lecture Notes in Computer Science, 2010)
This book constitutes the refereed proceedings of the 29th Annual International Conference on the Theory and Applications of Cryptographic Techniques, EUROCRYPT 2010, held on the French Riviera, in May/June 2010. The 33 revised full papers presented together with 1 invited lecture were carefully reviewed and selected from 188 submissions. The papers address all current foundational, theoretical and research aspects of cryptology, cryptography, and cryptanalysis as well as advanced applications. The papers are organized in topical sections on cryptosystems; obfuscation and side channel security; 2-party protocols; cryptanalysis; automated tools and formal methods; models and proofs; multiparty protocols; hash and MAC; and foundational primitives.